Co-Creating Snacks: A Cross-Cultural Study with Mediterranean Children Within the DELICIOUS Project - Elena Romeo-Arroyo; María Mora; Olatz Urkiaga; Nahuel Pazos; Noha El-Gyar; Raquel Gaspar; Sara Pistolese; Angelique Beaino; Giuseppe Grosso; Pablo Busó; Juancho Pons; Laura Vázquez-Araújo (Foods)
Mediterranean diet adherence has been decreasing during the last few decades, and non-appropriate snacking habits have also been identified among Mediterranean children and adolescents. To co-create new snacks and to explore children’s interests and preferences, a multi-method approach was used in the present study, including some qualitative and quantitative research phases. Conducted in collaboration with schools in Lebanon, Egypt, Portugal, Italy, and Spain, different snack prototypes were designed and tested in a Mediterranean cross-cultural context. The results showed significant differences among countries in snacking preferences and general food-related attitudes. Italian children exhibited higher levels of neophobia, resulting in lower acceptance of all proposed snacks. Some sensory and contextual insights were collected, such as Egyptian children favoring sweet and crunchy textures and “At school”, “With my friends”, and “As a morning/afternoon snack” being identified as linked to snack acceptance in some countries. The present study underscores the value of co-creation processes involving children to address non-recommended dietary patterns, highlighting the critical role of sensory properties, cultural differences, and contextual factors in designing healthy snacks that meet the Mediterranean diet’s principles but are highly appreciated by the young segment of the population.